2018
DOI: 10.1590/2317-1782/20182017063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between early and delayed facial nerve decompression in traumatic facial nerve paralysis - A retrospective study

Abstract: Purpose To study the intraoperative findings in case of early and delayed decompression of facial nerve paralysis and compare their results. Methods Retrospective data analysis of 23 cases of longitudinal temporal bone fracture with House-Brackmann grade V and VI facial nerve paralysis. All cases were thoroughly evaluated and underwent facial nerve decompression through the transmastoid approach. All cases were under regular follow-up till the date of manuscript submission. Results Clinical improvement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…[2,4,[12][13][14]17,20] ere are many reports that decompression was effective, especially when interventions were performed in the acute phase. [3,5,6,9,18,19] However, most patients with temporal bone fractures due to severe head injury suffer from intracranial or systemic complications and present with impaired consciousness. Facial nerve function assessment is challenging for patients with impaired consciousness, [1] and poor clinical conditions delay intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,4,[12][13][14]17,20] ere are many reports that decompression was effective, especially when interventions were performed in the acute phase. [3,5,6,9,18,19] However, most patients with temporal bone fractures due to severe head injury suffer from intracranial or systemic complications and present with impaired consciousness. Facial nerve function assessment is challenging for patients with impaired consciousness, [1] and poor clinical conditions delay intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 4 , 12 - 14 , 17 , 20 ] There are many reports that decompression was effective, especially when interventions were performed in the acute phase. [ 3 , 5 , 6 , 9 , 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…2,16,17 In a study, they stated that the surgery performed before 6 weeks had better results and that early treatment of bone spicules, slipped ossicles, and step deformities, and the fact that fibrosis in the nerve after 6 weeks prevented regeneration were effective in this result. 18 One review reported that patients who underwent surgery before 2 weeks had a better prognosis. 19 In addition, it has been reported that as the denervation time increases, muscle fibrosis and atrophy increase.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent facial palsy can occur in up to 7% of patients undergoing parotidectomy [6,7]. Another potential complication is paresthesia, also described in superficial parotidectomy.…”
Section: Introductionmentioning
confidence: 99%